Transparency in governments: a meta-analytic review of incentives for digital versus hard-copy public financial disclosures - Munoz, Laura Alcaide; Hernandez, Antonio Manuel Lopez; Bolivar, Manuel Pedro Rodriguez (2017)
Prior research has indicated that information transparency in governments depends on institutional and environmental factors. Nonetheless, previous studies show heterogeneity in the results, and the academic researchers cannot make consistent conclusions. It makes it difficult to know the behavior of governments regarding their information policies. Therefore, making use of meta-analysis techniques, we integrate the empirical results reported by studies to determine the factors favoring the disclosure of public financial information via two modes of information disclosure-online versus hard-copy format. Several moderating effects-administrative culture, accounting regime, impact of measure used on determining variables, and level of government-have been considered and analyzed for their influence on the degree of correlation between the determinants and the disclosure of public financial information in both modes of information disclosure. Our study does not only show that the variables analyzed are positively associated with the disclosure of public financial information, but also that this depends on the context in which the research is conducted. The administrative style and the level of government are the main moderating effects that influence the results of analyzed studies. - Reproduced.
Keywords: Budgetary control; E governance; Financial administration; Public administration